America Town : Building the Outposts of Empire - Gillem, Mark L. (Book collections on Project MUSE., 2007)
In America Town, Mark L. Gillem reveals modern military outposts as key symbols of not just American power but also consumer consumption. Through case studies of several U.S. military facilities Gillem exposes these military installations as suburban culture replicated in the form of vast green lawns, three-car garages, and big-box stores and questions the impact of this practice on the rest of the world.